IMPACT DES DETERMINANTS DE LA SANTE SUR LA FREQUENCE DES MALADIES INFANTILES EN REPUBLIQUE DEMOCRATIQUE DU CONGO Cas de la ville de Kindu en Province du Maniema durant la période quinquennale de 2018 à 2022 - SHINDANO, Joseph ISEGE (International Journal For Research In Health Sciences And Nursing, 2023)
This survey permitted to analyze thefrequency of the morbidity, to categorize the determinants of health and to diagnose the MID to the laboratory and to value thefrequency of the MID in Kindu. The infantile illnesses to diagnose is grouped in four categories notably the bacterial illnesses, the parasitic illnesses, the viral illnesses and the nutritional illnesses The determinants of health constitute a real publich ealth problem in Kindu (socioeconomic and environmental determinants).